Implications of phase difference and amplitude ratio from intracochlear and extracochlear electrocochleography in normal-hearing guinea pigs - van Beurden, Imogen A. M. L.; Ramekers, Dyan; Stokroos, Robert J.; Thomeer, Hans G. X. M.; Versnel, Huib (Frontiers in Neuroscience, 2026)
IntroductionElectrocochleography (ECochG) can be performed extracochlearly from the round window, as well as intracochlearly from an electrode array as used in cochlear implantation. Cochlear microphonic (CM) amplitude ratio and phase difference from two fixed intracochlear electrodes may improve insight into local cochlear trauma after cochlear implantation.MethodsSix normal-hearing guinea pigs underwent cochleostomy and cochlear implantation. ECochG was recorded in response to pure tones between 0.25 and 16 kHz from one extracochlear site El_Ex and two intracochlear sites: El_Ap and El_Bs. The CM was analyzed in terms of threshold, amplitude ratio and phase difference. Regarding the analyses of the latter we focused on CM at 2 and 4 kHz. The compound action potential (CAP) was analyzed in terms of threshold and amplitude. Histological trauma and hair cell counts were determined in midmodiolar sections.ResultsBoth CM and CAP thresholds from El_Ap were approximately 5–10 dB lower than from El_Bs (CM thresholds: p = 0.003, CAP thresholds: p = 0.03). Across frequencies 0.25–8 kHz, CM amplitudes from El_Ap were a factor 4–8 larger than amplitudes from El_Ex (p < 0.001) and a factor 2–4 larger than amplitudes from El_Bs (p < 0.001). Across frequencies 0.25–8 kHz CAP amplitudes from El_Ap were a factor 2 larger than amplitudes from El_Bs (p = 0.02). The CM amplitude ratios between both intracochlear electrodes varied among animals from 1.7 to above 10 (median amplitude ratio: 2 kHz = 6.86; 4 kHz = 3.56), and CM phase differences varied from near 0 to −π (median phase difference: 2 kHz = −0.13π; 4 kHz = −0.32π). Four different combinations of small or large CM phase difference and small or large CM amplitude ratio were identified. In all animals, hair cell counts were normal. Histological trauma in the lateral wall around the site of cochleostomy was mild in four animals and moderate in two animals.DiscussionIn addition to conventional electrophysiological thresholds, combinations of small or large CM phase difference and amplitude ratio from two intracochlear electrodes may mirror specific patterns of cochlear trauma as caused by cochlear implantation surgery.